Peran Humas Dalam Meningkatkan Mutu Pendidikan Dan Kepercayaan Masyarakat Terhadap Lembaga Pendidikan di MAN Bondowoso - Muhammad Fadali Amar; Muhib Ainul Yaqin; Durrotul Masruroh (CV Edujavare Publishing, 2026)
This research examines the importance of the role of public relations in promoting and improving the image of educational institutions, with a special focus on madrasas. Discusses communication strategies and public relations management, as well as the use of information technology in education. This study also highlights the impact of community participation in education and the role of public relations in improving the quality of education. This research uses a qualitative descriptive approach to analyze the impact of public relations on the quality of education and public trust located at MAN Bondowoso. Madrasah Aliyah Negeri Bondowoso is a practical example that shows efforts to change negative perceptions about madrasas and introduce this institution to the public. Supporting factors such as support from alumni and parents were identified, as well as inhibiting factors including dual roles as teachers and public relations, budget limitations, and inadequate facilities. The results of these efforts resulted in improving the quality of education and increasing public trust in madrasas. Overall, this research emphasizes the important role of public relations in improving the quality of education and growing public trust in educational institutions. This underlines the importance of community relations as a management function that fosters positive relationships between organizations and society, especially in the context of educational institutions.